Transformation of Goethite to Hematite Nanocrystallines by High Energy Ball Milling - O. M. Lemine (Advances in Materials Science and Engineering)
α-Fe2O3 nanocrystallines were prepared by direct transformation via high energy ball milling treatment for α-FeOOH powder. X-ray diffraction, Rietveld analysis, TEM, and vibrating sample magnetometer (VSM) are used to characterize the samples obtained after several milling times. Phase identification using Rietveld analysis showed that the goethite is transformed to hematite nanocrystalline after 40 hours of milling. HRTEM confirm that the obtained phase is mostly a single-crystal structure. This result suggested that the mechanochemical reaction is an efficient way to prepare some iron oxides nanocrystallines from raw materials which are abundant in the nature. The mechanism of the formation of hematite is discussed in text.